Chapter 8 Applying an integrated approach to workplace mental health in SMEs A case of the "too hard basket" or picking some easy wins? - Martin, Angela J. (Taylor & Francis, 2018)
Small-medium enterprises (SMEs) are a vital employment sector in most developed economies but these work settings have not featured widely in occupational health research and practice. Given the high prevalence of mental health disorders and their related economic consequences, mental health focussed interventions that are gaining traction in larger organizations also need to be on the agenda for SMEs. The potential for interventions in this sector is examined by reviewing a best practice framework, the integrated approach to workplace mental health and associated guidelines to assist organizations with implementation, in relation to the SME context and characteristics. Several promising opportunities and potential challenges are identified and researchers and practitioners are encouraged to focus greater attention on this sector, particularly around the issues identified.